Baccalaureate Speech - Magnuson, Nancy (My University, 2017)
College Librarian Nancy Magnuson, prior to her retirement after 30 years with the College, offers advice to the 2017 Goucher College graduates at Baccalaureate.
Keywords: Baccalaureate; Goucher College Library; Research; Reflection; Relationships; Resilience